2014
DOI: 10.1044/2014_aja-14-0008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Policy Changes to Universal Newborn Hearing Screening Follow-Up in a University Clinic

Abstract: Challenges remain in meeting the goals of amplification within 1 month of diagnosis and documenting the start of early intervention. Improved communication between and education of all parties involved in the care of infants is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Care coordination with pediatricians (Christensen et al 2008; Seeliger et al 2016; Zeitlin et al 2021), with diagnostic testing sites (Seeliger et al 2016; Al-Mulki & Todd 2020Al-Mulki & Todd 2020) and using hospital Child Find services to coordinate care has also been shown to improve diagnostic follow-up (Deem et al 2012). Proactively scheduling screening and diagnostic follow-up appointments at the time of need instead of shifting the responsibility to parents for calling to schedule at a later time significantly improves completion of follow-up (Krishnan & Van Hyfte 2014; Thomson & Tran et al 2017; Yoshinaga-Itano 2018; Zeitlin et al 2021). Lastly, partnering with community services like the Women, Infant, and Children (WIC) Program allows for better communication of needed follow-up and the potential for colocating follow-up services at appointments that are already being completed for infants who were lost to follow-up (Hunter et al 2016; Zeitlin et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Care coordination with pediatricians (Christensen et al 2008; Seeliger et al 2016; Zeitlin et al 2021), with diagnostic testing sites (Seeliger et al 2016; Al-Mulki & Todd 2020Al-Mulki & Todd 2020) and using hospital Child Find services to coordinate care has also been shown to improve diagnostic follow-up (Deem et al 2012). Proactively scheduling screening and diagnostic follow-up appointments at the time of need instead of shifting the responsibility to parents for calling to schedule at a later time significantly improves completion of follow-up (Krishnan & Van Hyfte 2014; Thomson & Tran et al 2017; Yoshinaga-Itano 2018; Zeitlin et al 2021). Lastly, partnering with community services like the Women, Infant, and Children (WIC) Program allows for better communication of needed follow-up and the potential for colocating follow-up services at appointments that are already being completed for infants who were lost to follow-up (Hunter et al 2016; Zeitlin et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies indicated several factors that could affect directly the length of the period between the diagnosis and initiation of education. The referral of the children to education by the health sector, the difficulties in scheduling the testing time, and absence of the patients were reported as main reasons for the increase in the time between the diagnosis and the intervention (Krishnan & Hyfte, 2014 drigues, Loiola-Barreiro, Pereira & Pomilio, 2015;McLean, Ware, Heussler, Harris & Beswick, 2019). Further research should be conducted to understand and explain the obstacles specific to Turkey, however clinical observations of the authors were consistent with previously reported findings that implied serious problems in the referral of the patients to education by the legal regulations, and the significant disorganization between the service providers (Baş et al, 2019;Kemaloğlu, 2015;Vehapoğlu-Türkmen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Before the universal newborn hearing screening (UNHS) program and genetic screening for deafness-susceptibility in newborns (GSDSN) program, children with severe and profound hearing loss could not receive proper diagnosis and management until age 3, while children with mild and moderate hearing loss would be diagnosed even later, which severely impacted the auditory and speech development of these children. [ 1 2 3 ] The development of UNHS program and GSDSN program allows infants and toddlers with hearing loss to enter the process of auditory and speech habilitation by receiving hearing aids (HA) and/or cochlear implantation (CI). [ 4 ]…”
Section: Introductionmentioning
confidence: 99%